2014
DOI: 10.1007/s11064-014-1460-6
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Homer1b/c in Neuronal Apoptosis Following LPS-Induced Neuroinflammation

Abstract: Homer, also designated Vesl, is one member of the newly found postsynaptic density scaffold proteins, playing a vital role in maintaining synaptic integrity, regulating intracellular calcium mobilization, and being critical for the regulation of cellular apoptosis. However, its function in the inflamed central nervous system (CNS) is not fully elucidated. Here, we investigated the role of Homer1b/c, a long form of Homer1, in lipopolysaccharide (LPS) induced neuroinflammation in CNS. Western blot analysis indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…Interestingly, knockdown of Homer1b/c significantly increased Bcl-2 and decreased Bax expression. Cui et al reported that upregulation of Homer1b/c was related to the subsequent apoptosis and downregulation of Homer1b/c, and decreased the proportion of Bax/Bcl-2 in neurons during neuroinflammation [17]. It suggested that Homer1b/c induced neuronal apoptosis through the Bax/Bcl-2 pathway in ALS, and knockdown of Homer1b/c partially suppressed mtSOD1 (G93A)-induced neuronal apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, knockdown of Homer1b/c significantly increased Bcl-2 and decreased Bax expression. Cui et al reported that upregulation of Homer1b/c was related to the subsequent apoptosis and downregulation of Homer1b/c, and decreased the proportion of Bax/Bcl-2 in neurons during neuroinflammation [17]. It suggested that Homer1b/c induced neuronal apoptosis through the Bax/Bcl-2 pathway in ALS, and knockdown of Homer1b/c partially suppressed mtSOD1 (G93A)-induced neuronal apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Homer1b/c constitutively expresses and has dimerization capacity, which causes signal transduction or crosstalk between target proteins in neurons. It acts as an important regulator of neurological, physiological, and pathological processes such as maintaining dendritic spine structure and synaptic function [17,18], regulating the activity and cell-surface clustering of metabotropic glutamate receptor (mGluR)1a/5 [15], mediating an important cellular mechanism that regulates metabotropic glutamate signaling [19], regulating intracellular Ca 2+ homeostasis [20], affecting mGluR1a/5-dependent synapse-to-nucleus communication and participating in glutamate-mediated excitotoxicity via endoplasmic reticulum and mitochondria pathways [21]. However, the role of Homer1b/c in ALS remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, upregulated Homer1a in astrocytes downregulated astrocytic glutamate release by precluding the mGluR5-mediated intracellular Ca 2+ signaling [ 11 ]. In contrast, the long Homer1 isoform, Homer1b and c, have been reported as promoters of neuronal apoptosis via a Bax/Bcl-2-dependent pathway [ 32 ]. Furthermore, the other long Homer isoforms, Homer2a, has been shown to be involved in apoptosis of cultured endothelial cells [ 33 ].These studies indicate that Homer proteins are associated with several signaling pathways related to apoptosis in neuronal and non-neuronal cells, and especially short Homer proteins may play an important role in protection from apoptotic cell death.…”
Section: Discussionmentioning
confidence: 99%
“…“Down-regulation of Homer1b/c could attenuate group I mGluR dependent Ca 2+ signaling through regulating endoplasmic reticulum Ca 2+ release and then protect neurons from glutamate excitotoxicity after injury” [ 116 , 117 ]. Homer1b/c promotes “neuronal apoptosis via the Bax/Bcl-2 dependent pathway during neuroinflammation in CNS, and inhibition of Homer1b/c expression may provide a novel neuroprotective strategy against the inflammation-related neuronal apoptosis” [ 118 ]. Up-regulation of postsynaptic Homer1a could protect against neuronal injury by reducing the level of phosphorylated extracellular signal-regulated kinase (ERK) and then disrupting mGluR-ERK signaling [ 119 , 120 ].…”
Section: Mglur Interacting Proteins As Therapeutic Targets In the Conmentioning
confidence: 99%